2004
DOI: 10.1245/aso.2004.05.013
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic Placement of Hepatic Artery Infusion Pumps: Technical Considerations and Early Results

Abstract: LHAIP placement is technically feasible, and variant HA is not associated with increased pump complications or decreased pump functional time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…One avenue of potential study involves the implantation of the infusion pump and whether implantation could be accomplished using a less invasive technique. Several alternatives to laparotomy have been explored, including laparoscopy, robot-assisted techniques, and percutaneous approaches [60][61][62][63][64][65][66][67][68] . All the techniques have clear advantages over the conventional approach, but none has demonstrated consistently acceptable results with respect to pump function and complication rates.…”
Section: Areas Of Future Studymentioning
confidence: 99%
“…One avenue of potential study involves the implantation of the infusion pump and whether implantation could be accomplished using a less invasive technique. Several alternatives to laparotomy have been explored, including laparoscopy, robot-assisted techniques, and percutaneous approaches [60][61][62][63][64][65][66][67][68] . All the techniques have clear advantages over the conventional approach, but none has demonstrated consistently acceptable results with respect to pump function and complication rates.…”
Section: Areas Of Future Studymentioning
confidence: 99%
“…1317 In this report, we provide a descriptive analysis of our series of robotic HAIP placements with a comparison to our open and laparoscopic experience at the MSKCC.…”
Section: Introductionmentioning
confidence: 99%
“…A minimally invasive pump placement using conventional laparoscopic techniques has been described in the literature [9][10][11][12]. Franklin et al reported a series of 20 laparoscopic pump placements during concurrent major laparoscopic procedures with no conversions and no intraoperative complications [10].…”
Section: Discussionmentioning
confidence: 99%
“…Franklin et al reported a series of 20 laparoscopic pump placements during concurrent major laparoscopic procedures with no conversions and no intraoperative complications [10]. Hansen et al reported one conversion due to dense adhesions, no intraoperative complications, and three catheter thromboses in a series of 38 patients [9]. The placement of a hepatic artery infusion catheter with conventional laparoscopic techniques is technically a very challenging procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation